Penyuluhan Penggunaan Kontrasepsi IUD Pada Wanita Usia Subur Sebagai Upaya Pengaturan Jarak Kehamilan Di PMB Sary Rahayu, S.ST Tahun 2024 - Silvia Finida Hannisa (Jurnal Kabar Masyarakat, 2024)
Family planning is an effort to measure the desired number and spacing of children in order to achieve a happy and quality small family. The Millennium Development Goals are the result of an agreement between 189 countries including Indonesia. This declaration contains the commitment of each country and the international community to achieve eight goals in 2015 as a package of measurable goals for development and poverty alleviation. So the government established a family planning program to prevent overcrowding by forming small, happy and high-quality families (WHO, 2017).